Wasatiyyah as Architectural Representation: The Case of Istiqlal Mosque - Eya Benlakhdhar; Ahmad Shaleh Amin (Badan Pengelola Masjid Istiqlal, 2024)
The principle of wasatiyyah—understood in Islam as the ethical path of balance, restraint, and justice—has been widely explored in theology, law, and moral philosophy. However, its translation into architectural practice, particularly in modern mosque design, remains insufficiently examined. This paper aims to investigate how wasatiyyah is materially and spatially embodied in the architecture of the Istiqlal Mosque in Jakarta, Indonesia, and to demonstrate that moderation can function as a rigorous design framework rather than a purely symbolic ideal. Using a qualitative, theory-driven case study approach, this research analyzes architectural drawings, historical records, scholarly literature, and spatial configurations of the mosque. The principle of wasatiyyah is operationalized through thematic categories—monumentality and humility, tradition and modernity, local climate and technological restraint, symbolic meaning and functional clarity—which are then applied to the mosque’s urban orientation, spatial hierarchy, material choices, stylistic synthesis, and environmental strategies. The findings reveal that Istiqlal Mosque performs wasatiyyah through a carefully balanced architectural system. Monumental scale is moderated by minimalist material expression; global Islamic symbols such as the dome are integrated with local climatic responsiveness; and modern structural technologies are employed without displacing ethical restraint. Rather than relying on the visual replication of historical mosque forms, Istiqlal conveys Islamic identity through proportional balance, spatial ethics, and environmental responsibility. This study argues that Istiqlal Mosque represents a paradigmatic model of architectural moderation, where wasatiyyah is not merely represented but actively enacted through design. By positioning wasatiyyah as an analytical lens for contemporary mosque architecture, this paper contributes to both Islamic thought and architectural theory, offering a framework for ethically grounded, context-sensitive religious design in the modern world.